SECURITY IN E-COMMERCE- A REVIEW OF LEGISLATIONS, CASES, GUIDELINES, POLICIES AND REGULATIONS - masaeed, Sultan Al; Johar; MGM; ALSoud, Anas Ratib (International Journal of Psychosocial Rehabilitation, 2020)
Doing business in the 21st century is distinctively different than of the previous century. With the rapid growth of the internet and the burgeoning use of information and communications technologies(ICT), commerce have changed in terms of its medium of trade and exchange. Commerce is now done electronically and it forms a major part of the ICT based economy. Electronic commerce or E-commerce uses the internet as its main medium of transaction, although there are other forms non-internet based transaction. The increase of business due to E- commerce is very encouraging and will be the mainstay of the global economy for many years to come. Nevertheless, the darker side of e-commerce exists. New breed of threats not seen in traditional form of commerce have come to existence. Nevertheless, it is always useful or vital for one to be armed with knowledge (especially with regards to the law) about safety and security issues in electronic commerce in order to ensure that doing business in the internet is a fruitful endeavor to ensure economic success (Barkatullah, 2018; De Silva et al., 2018a; De Silva et al., 2018b; Nikhashemi et al., 2013).